The Pimsner-Voiculescu sequence for coactions of compact Lie groups - Goffeng, Magnus (MATHEMATICA SCANDINAVICA, 2012)
The Pimsner-Voiculescu sequence is generalized to a Pimsner-Voiculescu tower describing the KK-category equivariant with respect to coactions of a compact Lie group satisfying the Hodgkin condition. A dual Pimsner-Voiculescu tower is used to show that coactions of a compact Hodgkin-Lie group satisfy the Baum-Connes property.